A Survey on Vertical and Horizontal Scaling Platforms for Big Data Analytics - Ali, Ahmed Hussein (International Journal of Integrated Engineering, 2019)
There is no doubt that we are entering the era of big data. The challenge is on how to store, search, and analyze the huge amount of data that is being generated per second. One of the main obstacles to the big data researchers is how to find the appropriate big data analysis platform. The basic aim of this work is to present a complete investigation of all the available platforms for big data analysis in terms of vertical and horizontal scaling, and its compatible framework and applications in detail. Finally, this article will outline some research trends and other open issues in big data analytics